Managing Kano Zoo for Sustainable Tourism in Nigeria: Implications on Wildlife Conservation - Bunza, Mustapha Sani; Alarape Abiodun, Abideen; Adewale, Rilwan Oluyinka; Dododawa, Zubeiru (Academia Journal of Humanities & Social Sciences, 2025)
The zoological gardens are set up to enlighten the public on the importance of conservation, but it is still not clear how successful their operations are in Nigeria. Thus, a study on the management of Kano Zoo for sustainable tourism in northwest Nigeria was conducted with the goal of evaluating the facilities within the zoo for the sustainable use of wildlife resources and management implications on conservation. Data were collected through a semi-structured questionnaire and direct observation. A total of 174 questionnaires were used, of which 100 were given to the visitors and 74 to the zoo employees. The findings of the study suggest that a significant association exists between visitors’ satisfaction and animal variety in the zoo (χ2=53.07a), facilities and satisfaction (χ2=37.28a), cleanliness of the area and satisfaction (χ2=28.23a), clear signage and satisfaction (χ2=49.33a). The results further revealed that 50% of the visitors prefer the use of guided tour strategy during environmental education. The staff-visitor relationship was rated high by the majority (67.4%) of the visitors. Most (73%) of the staff-visitor conflicts were attributed to the disregard for rules by the visitors. Teasing of animals and littering of the environment were the most common (56.7%) reported offenses. Finally, it is imperative that the tourists should be made aware of the importance of conservation.